Preparasi Katalisator Berbasis Biochar dari Ampas Buah Merah untuk Reaksi Transesterifikasi Minyak Jelantah - Rahmah, Puspa; Yuliansyah, Ahmad Tawfiequrrahman; Wintoko, Joko (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Biodiesel can be produced from plant and animal oils by transesterification reaction using homogeneous or heterogeneous catalysts. In this study, we prepare a biochar-based catalyst, as a heterogeneous catalyst, for transesterification of used cooking oil. The biochar was made by the pyrolysis of the solid waste from the oil extraction of Papuan red fruit (Pandanus conoideus). After the pyrolysis, the solid was immersed in KOH solution to provide the kalium in the produced biochar. The biochar was then sulfonated by H2SO4 5M for 15h at 120°C. Afterwards, the catalysts were characterized by BET for surface area measurement, FTIR for functional groups on the catalyst surface determination and XRD for successive crystallography characterization. The catalytic performance was studied by conducting transesterification of used cooking oil using methanol with the prepared biochar-based catalysts. The transesterification optimum conditions were found to be oil to methanol molar ratio of 1:15, temperature of 60°C, reaction time of 2 hours and the catalyst amount of 3% of the oil weight. Furthermore, the highest biodiesel yield was obtained by the catalyst prepared from biochar that was sulfonated with 5M H2SO4 solution